Penentuan Wilayah Pemasaran Kopi Colol Dengan Metode AHP-TOPSIS - Andryana, Septi; Andani, Angela Nerci (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Colol is the centre of high-quality coffee production in Manggarai, NTT. Colol's arabica and robusta coffee won the title of best coffee in the 2015 coffee contest, organised by the Indonesian Coffee Exporters and Industry Association in collaboration with coffee research and Akao Jember. From 2017 until now, Robusta coffee exports to the Netherlands have continued, with a grand total of 94 tonnes. However, Colol Coffee is not widely known by people outside NTT, so this study aims to determine the marketing area of colol coffee outside NTT with the criteria of Accessibility, Market Potential, Logistics, Environmental Conditions, and Security, by considering 9 alternative regions. Multi-criteria decision making (MCDM) involves evaluating decision alternatives with multiple criteria that have different weights according to their importance. The research method uses Analytical Hierarchy Process (AHP) to determine the criteria weights and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) to analyse and rank the region alternatives based on their closeness to the ideal solution. The data collection technique uses the interview method with related parties, namely ASNIKOM managers who are decision makers and literature studies as a source of in-depth data that provides a theoretical basis to support the decisions taken. The results showed the highest priority value in the regions of Bali (0.7068), DKI Jakarta (0.5930), West Nusa Tenggara (0.5877), Central Java (0.5762), West Sumatra (0.5651), East Java (0.5298), North Sumatra (0.4284), West Java (0.4003), South Sumatra (0.3095).